2019
DOI: 10.1039/c9dt02052g
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxometalate-based high-spin cluster systems: a NMR relaxivity study up to 1.4 GHz/33 T

Abstract: Paramagnetic polyoxometalates are of special interest with regard to their application as alternative contrast agents in nonhuman magnetic resonance imaging which is increasingly used in materials science and process engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 27 publications
1
20
1
1
Order By: Relevance
“…Having shown the basic suitability of the POMs to serve as CA in aqueous solutions, the dispersion of the longitudinal and the transverse relaxivities were investigated while the 1 H Larmor frequencies ν 0 corresponding to magnetic fields ranged from 20 MHz up to 1.2 GHz in the present study. The experimental details of the NMR measurements have been described previously in detail in [13][14][15]. Essentially, NMR systems based on permanent magnets (≤ 80 MHz), on superconducting magnets (≤ 400 MHz) and on high-power (24 MW) electromagnets (≥ 800 MHz) were used to measure the relaxivities of the POMs.…”
Section: Pre: Paramagnetic Relaxation Enhancementmentioning
confidence: 99%
See 3 more Smart Citations
“…Having shown the basic suitability of the POMs to serve as CA in aqueous solutions, the dispersion of the longitudinal and the transverse relaxivities were investigated while the 1 H Larmor frequencies ν 0 corresponding to magnetic fields ranged from 20 MHz up to 1.2 GHz in the present study. The experimental details of the NMR measurements have been described previously in detail in [13][14][15]. Essentially, NMR systems based on permanent magnets (≤ 80 MHz), on superconducting magnets (≤ 400 MHz) and on high-power (24 MW) electromagnets (≥ 800 MHz) were used to measure the relaxivities of the POMs.…”
Section: Pre: Paramagnetic Relaxation Enhancementmentioning
confidence: 99%
“…Concerning adjustment of dose or concentration, new classes of contrast agents with improved relaxivity can be designed by incorporating high numbers of paramagnetic centers within the same molecule or cluster that in turn means that lower doses can be given to produce marked alterations in contrast [7,12]. Up till now, the NMR relaxivities of ultra-high ground spin state cyclic coordination clusters based on 3d and 4f ions [Fe III 10 Ln III 10 (Me-tea) 10 (Me-teaH) 10 (NO 3 ) 10 ] (Ln = Dy, Gd; Me-tea = triethanolamine) were studied over a wide range of 1 H Larmor frequencies from 10 MHz up to 1.4 GHz [13,14] and the PRE properties of polyoxometalate (POM) clusters containing both 3d and 4f paramagnetic ions {Ln 30 Co 8 Ge 12 W 108 O 408 } {Ln 30 Co 8 }(Ln = Gd, Dy) were studied as well up to 1.4 GHz [15]. These investigations revealed that the relaxivities of these clusters containing a large number of paramagnetic centers are in sum much higher than the commercially available, often Gd-based medical contrast agents with only one paramagnetic center.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Until now, there are only a few reports on the sandwich-type Ln-POM family, where lanthanide metal centers (Ln III nuclearity ≥ 2) are sandwiched between two lacunary POM ligands [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Lanthanide-containing POM assemblies have demonstrated outstanding properties in various fields of research such as molecular magnetism [ 27 ], imaging [ 28 ], photoluminescence [ 29 ], catalysis [ 30 , 31 ] and electrochemistry [ 32 ]. Magnetic POMs have attracted an increasing interest after the discovery of the first POM-based single molecule magnet (SMM) [ErW 10 O 36 ] 9– [ 33 ].…”
Section: Introductionmentioning
confidence: 99%